AN ANALYSIS OF STUDENTS’ ABILITY IN LISTENING COMPREHENSION AT FIRST GRADE OF SMK NEGRI 1 BETARA IN ACADEMIC YEAR OF 2017/2018 - Ahmad Akbar; Suyadi Suyadi (Universitas Batanghari Jambi, 2019)
The purpose of the research is want to know the students’ ability in listening comprehension at second year students of SMK Negeri 1 Betara academic year 2017/2018 and the factors that influence in learning listening comprehension in SMK Negri 1 Betara. The design of this research was quantitative research. The Population was the first grade students of SMK N 1 Betara in academic year 2017/2018. There were 31 students and engineering was taken as the sample classes. The students were given listening test by multiple choices. The students were chosen the questions by knowledge. The information in details in reference. Moreover, it was also proven by the result of the total percentage of the students with the researcher found zero students with the interval 81-100%. There were that percentage (0%) classified in excellent level. In good level, there were five students that percentage (0%) too. There were twenty six students that percentage (85%) in sufficient level. In poor level there were five students that percentage (15%) and zero students who got very poor level and Mean of the students was 52. based on the result of data analysis, it was concluded that generally the students ability in listening comprehension at first grade students of SMK NEGERI 1 Betara in Academic Year2017/2018 was sufficient